Russia, Eurasia and the New Geopolitics of Energy
256 p.
Keywords: By combining perspectives from experts in domestic politics, regional politics, and specialists in international security, this edited volume focuses on the central role of energy production and supply in the Russian-Western completion across Eurasia.